2002
DOI: 10.1037/0033-2909.128.6.934
|View full text |Cite
|
Sign up to set email alerts
|

Belief and feeling: Evidence for an accessibility model of emotional self-report.

Abstract: This review organizes a variety of phenomena related to emotional self-report. In doing so, the authors offer an accessibility model that specifies the types of factors that contribute to emotional self-reports under different reporting conditions. One important distinction is between emotion, which is episodic, experiential, and contextual, and beliefs about emotion, which are semantic, conceptual, and decontextualized. This distinction is important in understanding the discrepancies that often occur when peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

74
1,404
7
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,500 publications
(1,512 citation statements)
references
References 212 publications
74
1,404
7
14
Order By: Relevance
“…People's representations of past events may be partly or wholly comprised of current knowledge, attitudes, and experiences (e.g., Bartlett, 1932;Loftus & Palmer, 1974;Schacter, 2001). Similarly, as memory for past feelings becomes inaccessible over time, people rely on salient information to reconstruct how they must have felt (Robinson & Clore, 2002a, 2002bRoss, 1989;Levine, 1997). We proposed that the magnitude and direction of bias in reports of the intensity of past feelings depends on whether people are remembering emotion (feelings about a specific event) or mood (feelings that are not about a specific event).…”
Section: Discussionmentioning
confidence: 99%
“…People's representations of past events may be partly or wholly comprised of current knowledge, attitudes, and experiences (e.g., Bartlett, 1932;Loftus & Palmer, 1974;Schacter, 2001). Similarly, as memory for past feelings becomes inaccessible over time, people rely on salient information to reconstruct how they must have felt (Robinson & Clore, 2002a, 2002bRoss, 1989;Levine, 1997). We proposed that the magnitude and direction of bias in reports of the intensity of past feelings depends on whether people are remembering emotion (feelings about a specific event) or mood (feelings that are not about a specific event).…”
Section: Discussionmentioning
confidence: 99%
“…Situation-specific measures of positive and negative emotions are needed to study co-ocurrences in this more narrow meaning -different emotions experienced at the same time. It has been argued that asking participants in retrospective questions to mentally aggregate their experiences over time may lead to memory biases and self-belief biases, and therefore be less valid than in-the-moment measures of emotions (see e.g., Goetz et al, 2013;Robinson & Clore, 2002;Takarangi et al, 2006). To address this limitation of the present study, Study 2 used in-the-moment measures of emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported retrospective experiences may be biased and, therefore, may reduce validity (Schwarz 2007), because older people may have difficulties in recalling events, behaviors, and feelings they experienced months ago. Subjective experiences, including the intensity of feelings, are poorly represented in memory: Once the experience ends, its characteristics can no longer be directly examined (Robinson and Clore 2002) and, therefore, respondents need to again rely on fragmentary recall. It can be concluded that if the study had been conducted in real time or immediately after the military operation the responses might have been somewhat different and more valid.…”
Section: Research Limitationsmentioning
confidence: 99%